OBSTACLES OF STUDENTS IN WRITING THE THESIS FINAL PROJECT IN THE STUDY PROGRAM OF IPS EDUCATION FACULTY OF SOCIAL SCIENCES AND LAW, STATE UNIVERSITY OF MAKASSAR - Yosie Esa Gistavia (Universitas Negeri Makassar, 2022)
This study aims to find out 1) the inhibiting factors of students that affect the writing of the thesis final project in the Social Sciences Education Study Program, Faculty of Social Sciences and Law, Makassar State University during the process of preparing the thesis final project. 2) The obstacles faced in writing the final thesis of students in the Social Sciences education study program, Faculty of Social Sciences and Law, Makassar State University during the process of preparing the thesis. 3) The impact of student barriers in writing the final thesis of students in the Social Sciences education study program, Faculty of Social Sciences and Law, Makassar State University when the process of preparing the thesis final project. The type of research used by the researcher is qualitative. as for data collection techniques through documentation, observation and interviews. The data collection process used by the researcher includes: data collection, word reduction, data presentation and drawing conclusions. The results of the study show that the obstacles in writing the final thesis in the Social Studies Education Study Program are divided into two, namely 1) Internal such as motivation or encouragement and also activities or busyness. 2) External, such as the administrative process and the guidance process with the supervisor. The impact of these obstacles has an impact on students' psychology which creates inner pressure from people around, so that students feel pressured and then try to avoid this pressure by looking for other activities.